Epistemic Erotetic Search Scenarios - Łupkowski, Paweł; Majer, Ondrej; Peliš Michal; Urbański, Mariusz (Logic and Logical Philosophy, 2018)
The aim of this paper is to introduce erotetic search scenarios known from Inferential Erotetic Logic by using the framework of epistemic erotetic logic. The key notions used in this system are those of askability and epistemic erotetic implication. Scenarios are supposed to represent all rational strategies of an agent solving the problem posed by the initial question where the interaction with an external information source is seen as a series of updates of the agent’s knowledge.